Moderated Politeness in the Digital Era: A Study of Digital Literacy in the Discourse of the 2024 Presidential Debate - Firdaus, Muhammad Anas; Prayitno, Harun Joko; Sulistyono, Yunus (Universitas Muhammadiyah Malang, 2025)
The development of digital social media has transformed patterns of political communication, particularly in the discourse surrounding the 2024 presidential debate, which often triggers polarization and neglects the principles of politeness. In this context, digital literacy plays a vital role in maintaining the quality of online interaction. This study aims to examine the forms of moderated politeness used by netizens and assess their levels of digital literacy within the 2024 presidential debate on social media. Using a qualitative descriptive approach, this research analysed 51 posts and comments from X, Instagram, and TikTok, based on Leech’s politeness maxims and Rheingold’s digital literacy indicators. The data were collected through observation, tapping, non-participatory observation, and note-taking, then analysed using a pragmatic identity method. The findings reveal that the maxim of approbation is the most dominant form of politeness as an expression of affirmative support, while the maxim of modesty is the least observed due to the competitive nature of digital political discourse. Network awareness emerged as the highest digital literacy indicator, whereas collaboration ranked the lowest due to limited active participation and one-way communication tendencies. This study offers a theoretical contribution by formulating an integrative cyber-pragmatic moderation model demonstrating that rhetorical choices and digital literacy skills shape digital political interaction in creating polite and productive discourse.